Question:Evaluate 7`xx`19.3+8`xx`19.3-5`xx`19.3
Answer
7`xx`19.3+8 `xx` 19.3 - 5`xx`19.3 =19.3(7+8-5) =19.3 `xx`10 =193
Question:Evaluate 7`xx`19.3+8`xx`19.3-5`xx`19.3
7`xx`19.3+8 `xx` 19.3 - 5`xx`19.3 =19.3(7+8-5) =19.3 `xx`10 =193
Question:Evaluate 19.3`pi` - 15.8`pi`
19.3`pi` - 15.8`pi` =`pi`(19.3-15.8)=`pi` `xx`3.5 = `22/7 xx 7/2` = 11
Question:Factories ax+bx+ay+by
ax+bx+ay+by = (ax+bx) + (ay+by) = x(a+b) +y (a+b) =(a+b) (x+y).
Question:Factorise ax + ay -x -y .
ax + ay -x -y=a(x+y) - (x+y) =(x+y) (a-1). Notice that when the last two terms are grouped with a minus sign outside. the signs of both terms in the bracket must be changed. ax + ay -x -y=a(x+y) - (x+y) and not a(x+y) - (x-y) . It is good plan to remove the brackets mentally to check your working.
Question:Factorise `xx^2`y - `xxy^2`+3y -3`xx`
`xx^2`y - `xxy^2`+(3y -3`xx`) = xy(x-y) +3(y-x) This has no obvious factor as the expression inside the brackets are different . but if we arrange the expression as `xx^2`y - `xxy^2`-3`xx`+3y) = `xx`y(x-y) -3(x-y), An obvious factor is now apparent. The factors are (x-y)(xy-3).